Formulation development of directly compressed Naproxen SR tablet using Kollidon SR and Avicel PH 102 polymer - Yasmin, Dilshad; Rahman, Md. Rashidur; Akter, Morshada (International Current Pharmaceutical Journal, 2013)
Naproxen is a well-known non-steroidal anti-inflammatory drug (NSAID). This work has been done for developing a formulation of 280 mg sustained release (SR) tablet where 150 mg active pharmaceutical ingredient (Naproxen) were used along with other excipients like Kollidon SR, Avicel PH 102, Lactose MH, Povidone K 30 and Mg-Stearate. Naproxen SR tablet was prepared by direct compression method aiming to enhance its dissolution properties. The physical parameters (hardness, thickness, diameter, average weight and friability) and drug release profile of this tablet were evaluated. The hardness of tablets from F1 and F2 formulation were highest and rest of them was also satisfactory. F2 formulation did not meet the friability test. But rests of the formulations were acceptable which indicate that others formulations can handle pressure during storage, transportation and packaging. All the formulations released 90% of drug within 120 minutes except F4 formulation. Among the six formulations, release was prompt in F1 formulation because of usage of higher concentration of polymer Kollidon SR. The outcome of this study indicates that the rate of dissolution of Naproxen SR tablet can be considerably improved with Kollidon SR. DOI: http://dx.doi.org/10.3329/icpj.v2i6.14871 International Current Pharmaceutical Journal, May 2013, 2(6): 112-114